Improving The Quality of Education in A Collection of Poems Pada Suatu Musim by Bayu Suta Wardianto in Quality Education - Irma Widiastuti , Ade; Ma'ruf , Amin; Muktiyusrina, Evalasefa; Wulan Nurlaili, Fadilah; Awaliyah Nur Kamila Hakim, Hilda; Dhiya Ulhaq, Wafly; Nuraeni, Weni (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
Education is an effort to improve the quality of life and human resources. Because education is the spearhead of a country to educate the nation's children. One of the goals of education is to increase student creativity in learning at school. Education based on local culture with various wisdom will be better for shaping character and developing self-potential than education sourced from cultures outside students. Education is the learning of knowledge, skills, and habits of a group of people passed from one generation to the next through teaching, training, or research. The etymology of the word education comes from the Latin ducare, meaning